PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SD NEGERI 018 UKUI 1 KECAMATAN UKUI - Narko (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by low Civics learning outcomes among students. The low achievement was caused by several factors: (a) students did not pay sufficient attention to Civics lessons and tended to talk to one another while the teacher was explaining; (b) students were not actively involved in the learning process; (c) when the teacher asked questions, only a few students responded; and (d) only a small number of students asked questions about material they did not understand. In addition, classroom learning activities were largely teacher-centered, resulting in limited student participation. This study aimed to improve Civics learning outcomes through the implementation of the cooperative learning model Numbered Heads Together (NHT). The research employed classroom action research conducted at SD Negeri 018 Ukui, Ukui Subdistrict. The study focused on data related to students’ Civics learning outcomes. The results of the study indicated an improvement in students’ Civics learning outcomes. This was evidenced by an increase in the number of students achieving mastery: in the preliminary data, only 15 students (50%) met the passing criteria; this number increased to 26 students (87%) in the first cycle and further rose to 27 students (90%) in the second cycle. Based on these findings, it can be concluded that the cooperative learning model NHT effectively improves Civics learning outcomes.